A Systematic Review: Local Literature in Integrated Skills for English Teaching - Leni Kicha (Journal of English Language Teaching, Literature and Culture, 2023)
The potential of local literature as a source of language learning which is rich, vibrant, and more spontaneous to teach and as a medium to develop literacy as well as to instil local values is overlooked in teaching English in Indonesia including teaching English for young learners. This study intended to understand how local literature can using in integrated skills of teaching English. This study also discusses the incorporation of local cultural material in a teaching material developed for the students. In this article, the writer focus only on systematic review from some article that related to local literature in integrated skills of teaching English. Finally this article reviews the past and current approaches to teaching literature in language teaching classes. Through local literature the writer hopes to improve students' abilities in reading, listening, writing and speaking skills, all of which are summarized in an integrated skills approach.